Professional life cycle of Pedagogical Advisors in higher education: an analysis from the configuration of a learning community for the function - Xavier, Amanda Rezende Costa (2025)
This article presents the results of empirical research developed in the context of a post-doctorate in University Pedagogy, which had as its object of study the pedagogical advisory service in Brazilian higher education institutions. It seeks to characterize a group that brings together pedagogical advisors from all over Brazil, culminating in the possibility of theorizing the professional life cycle in this service, given that the service has proven to be essential for the review and qualification of transversal pedagogical processes that take place in higher education, endorsing the need to create a theoretical corpus that expands the basis on which the pedagogical advisory service is developed at this level of education. The empirical research was developed between the years 2021 and 2022, based on the application of structured questionnaires to pedagogical advisors belonging to the University Pedagogical Advisory Study Group (GEAPU), which brought together more than 160 pedagogical advisors from institutions across Brazil, at the time of the collection, this group being, therefore, the locus for carrying out the research. The results, analyzed in light of theoretical production in the field of University Pedagogy, allow us to refine the understanding of the position occupied by such a service, both geographically and professionally, leading to an analytical possibility about the life cycle of the work perceived by pedagogical advisors.